The Impacts of Government Policy on Covid-19 to Airlines Liability: A Case Study in Indonesia - Elfrida Ratnawati (Jambura Law Review, 2021)
The impact of Covid-19's impact on the air transportation sector, especially in Indonesia. This article will discuss the impact and responsibility of airlines on the policies adopted by the Indonesian government regarding the COVID-19 pandemic. This article uses a normative juridical legal approach, research based on literature or secondary material. Meanwhile, the data obtained through legal analysis and social phenomena that occur in society. The rules that must be obeyed by airlines require them to do flight restrictions and cancellations. As a consequence of the cancellation, the airline must return the funds to passengers who have purchased travel tickets and the airline cannot hide behind force majeure. As the party issuing policies, the Government must be able to see a balance in social life and provide appropriate legal protection. In addition, the Government may not issue policies that can lead to different interpretations of those who read the policies. These strict regulations are needed so that passenger rights can be realized which is the responsibility of the airline.